2016
DOI: 10.1177/0735633116671324
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement and Dimensionality of Mobile Learning Systems Success

Abstract: The main purpose of this study is to develop and validate a multidimensional instrument for measuring mobile learning systems success (MLSS) based on the previous research. This study defines the construct of MLSS, develops a generic MLSS instrument with desirable psychometric properties, and explores the instrument's theoretical and practical applications. By analyzing data from a calibration sample (n ¼ 241) and a validation sample (n ¼ 209), this study proposes a 6-factor, 25-item MLSS instrument. This empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…From literature review, 5 factors were identified that is Attitude (ATT), System Quality (SQ), Information Quality (IQ), User background (UB), System Use (USE) to measure User satisfaction (US) and 4 factors that is ATT, SQ, IQ and UB to measure System Use. The questionnaire items with validated scales were adopted from [13]- [17] to form a 44 item questionnaire survey. A questionnaire survey was used to quantitatively answer 9 hypotheses created in regard to factors that will influence use and user satisfaction of the ETL register.…”
Section: Methodsmentioning
confidence: 99%
“…From literature review, 5 factors were identified that is Attitude (ATT), System Quality (SQ), Information Quality (IQ), User background (UB), System Use (USE) to measure User satisfaction (US) and 4 factors that is ATT, SQ, IQ and UB to measure System Use. The questionnaire items with validated scales were adopted from [13]- [17] to form a 44 item questionnaire survey. A questionnaire survey was used to quantitatively answer 9 hypotheses created in regard to factors that will influence use and user satisfaction of the ETL register.…”
Section: Methodsmentioning
confidence: 99%
“…Selected researchers applied the D&M model in online learning systems such as Massive Open Online Courses (MOOCs), mobile learning systems, and blog-based learning systems [25,26]. Based on the D&M theory, Wu and Chen [27] applied the structure equation model and multiple group analysis method to a Facebook system, and the result showed that social influence and information quality are critical and direct determinants that affect users' continuous intention to use Facebook in learning.…”
Section: Statistical Methods For the Dandm Modelmentioning
confidence: 99%
“…In the step, we can use Equations (25) and (26) to compute the rough proximity degree between the current level and aspiration level for alternatives.…”
Section: The Copras-r Methods With Aspiration Levelmentioning
confidence: 99%
“…The information system success model has been widely used to investigate satisfaction and continue use in numerous information systems contexts such as e-commerce (Wang, 2008);e-government(Wang&Liao,2008);mobilelearningsystem(H.-H. Lin,Wang,Li,Shih,&Lin, 2017) Alongsidethenotionofassumptionchallenging,thispaperalsoemploysgap-spotting,whichisan elementofresearchinvestigationwithintheremitofneglectspotting(Nicholsonetal.,2018).These twoapproacheswerechosenforanumberofreasons,firstlywithintheareaofMBandinformation systemsalotofthetraditionalliteraturedoesnotgofarenoughinchallengingthecurrentthinkingin thisarea,andsecondly,thedevelopmentofrevelatorycontributionscancreatenewwaysofknowing.It isimportanttonotethatwhiletheseapproachesarerelativelynew,theydonothavetoberevolutionary orgroundbreaking,inmanycasesitcanchallengemoderateassumptionswithinexistingtheoriesor intellectualtraditions (Sandberg&Alvesson,2011).Tohighlightourstrategies,Figure2illustrates theuseofassumptionchallengingandgapspottingindevelopingthepaper'scontributions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%